The Study of Early Childhood Character in Semurup Rawa Pening Hamlet Semarang Regency - Fatmawati, Nofi; Pranoto, Yuli Kurniawati Sugiyo (BELIA: Early Childhood Education Papers, 2020)
Semurup Hamlet is a tourist village located in the Rawa Pening area of Semarang Regency. As a tourist village with a large number of visitors, it has an influence on the character development of early childhood. This study aims (1) to know and describe the character of independence, responsibility, religion, and courtesy of early childhood, (2) to find out and describe the efforts of parents and the community in educating the character of early childhood, and (3) to know and describe the obstacles faced by parents and the community in educating the character of early childhood in the Semurup Hamlet, Semarang Regency. This study uses a qualitative descriptive research method. Data collection techniques are interviews, observation, and documentation. The obtained data is examined for the validity of the data by triangulation of data sources and methods. The results showed that (1) early childhood in Semurup Hamlet have the character of positive and negative independence, positive responsibility, positive religious, and positive and negative manners, (2) efforts made by parents in educating the character of children early by habituating, giving examples, and giving rewards, while community efforts are to provide advice and support for every educational activity, (3) obstacles that are experienced by parents in educating the character of the age child are internal factors including busyness of parents and the age of child, external factors include the influence of the environment around the residence and the development of information and communication technology, while the obstacle faced by the community is communication with parents.